E-023 Predictors of outcomes in tandem anterior circulation occlusions following mechanical thrombectomy. (23rd July 2022) - Catapano, J; Farhadi, D; Naik, A; Koester, S; Winkler, E; Srinivasan, V; Karahalios, K; Rulney, J; Desai, S; Jadhav, A; Albuquerque, F; Ducruet, A
Abstract : Background: Mechanical thrombectomy is the standard of care for large vessel occlusions. Tandem anterior circulation occlusions are particularly ominous, often requiring angioplasty and/or stenting of the extracranial lesion. Controversy remains regarding appropriate management for anterior circulation tandem occlusions requiring mechanical thrombectomy. Herein, predictors of outcome are analyzed for these challenging lesions. Methods: A retrospective analysis of all patients that were managed with an anterior circulation tandem mechanical thrombectomy from 1/1/2014 to 5/31/2020 at a single comprehensive stroke center. Patient demographics, occlusion characteristics, intraoperative/post-operative management, and in-hospital/discharge outcomes, were abstracted from the medical record of eligible patients. Outcomes analyzed included intracerebral hemorrhage, symptomatic intracerebral hemorrhage, TICI score, and discharge NIHSS. For univariate analysis, Welch's two-sample t-test for continuous data and chi-squared test for frequency-based variables were used. Multivariate analysis used multivariate linear and Firth's logistic regression. Results: During the study period, 54 patients were identified with an anterior circulation tandem occlusion undergoing a mechanical thrombectomy. The average age was 66.5 (SD = 13.10), and 65% were male. 72=% of patients had hypertension, 35% had atrial fibrillation. 17% had a prior history of stroke. 92% had a baseline modified Rankin Scale (mRS) of ≤ 2. The average initial National Institutes of Health Stroke Scale (NIHSS) score was 15.41 (SD = 6.69) at presentation. Intravenous TPA was given in 44.4% prior to the intervention. The mean post-treatment infarction volume was 71.53 ±85.00 mm. Concomitant intracranial M1 occlusion was observed in 75% of patients. 83% of patients had good reperfusion (TICI ≥ 2B). Discharge NIHSS was 10.3 ±7.4. On multivariate analysis, male sex, hyperlipidemia, prior history of anticoagulant use, and extracranial stenting was associated with increased risk of any intracerebral hemorrhage (ICH) on post-operative computed tomography (CT). However, only infarct volume (OR = 1.02, 95% CI: 1.00–1.06, p = 0.03) was associated with symptomatic ICH. Extracranial stenting was associated with a significantly greater odds of good final reperfusion (TICI ≥ 2B, OR = 28.694, p = 0.014). Predictors of the number of passes required included prior anticoagulation use and concomitant M1 occlusion (OR = 2.72, 1.611, p < 0.05, respectively). Post-procedure infarct volume and initial NIHSS were also predictors of discharge NIHSS (p = 0.02). When investigating optimal thresholds for predicting ICH following stenting, a threshold of 118.5 mm predicted symptomatic ICH (AUC = 0.915, accuracy = 92%). Discussion: In this study, we present outcomes of patients undergoing tandem mechanical thrombectomy. We demonstrate that stenting is associated with improved final reperfusion, but increased odds of asymptomatic ICH. Additional clinical trials should be performed to optimize the procedure and improve patient outcomes. Disclosures: J. Catapano: None. D. Farhadi: None. A. Naik: None. S. Koester: None. E. Winkler: None. V. Srinivasan: None. K. Karahalios: None. J. Rulney: None. S. Desai: None. A. Jadhav: None. F. Albuquerque: None. A. Ducruet: None.